Effects of two sources of Mexican oregano oil on performance, blood profile, carcass variables, and meat of broilers - Silva-Vázquez, Ramón (2018)
The current study was conducted to investigate the effects of Mexican oregano essential oil (MOO) extracts from Lippia berlandieri Schauer (LBS) and Poliomintha longiflora Gray (PLG) on performance, blood profiles, carcass variables, and meat composition of broilers at slaugther. A total of 360 one-day-old Ross broilers were randomly distributed into four dietary treatments with six replicate pens per treatment and 15 birds per pen. The dietary treatments were: a basal diet (control), control + 0.40 g of LBS/kg of feed, control + 0.40 g of PLG/kg, and control + 0.40 g of LBS/kg + 0.40 g of PLG/kg. Results showed that linear, quadratic, and cubic effects of days were significant in the performance variables of broilers. The treatments with LBS and PLG maintained the broiler body weight without increasing feed intake and water intake when compared with the control group. Broilers given LBS+PLG and PLG had increased blood leukocytes, lymphocytes, lowdensity lipoprotein, and hot carcass yields. In meat composition, treatments with PLG and LBS+PLG presented similar breast protein content compared with the control treatment. Supplementation with these two MOO exhibits positive effects on broiler performance, blood profiles, carcass traits, and meat composition. These two MOO may be promising feed supplements as growth promoters and enhancers of meat quality in broiler production